Membrane lipid remodeling and autophagy to cope with phosphorus deficiency in the dinoflagellate Prorocentrum shikokuense - Li, Da-Wei; Tan, Jin-Zhou; Li, Zhuo-Fan; Ou, Lin-Jian (Chemosphere (Oxford), 2024)
Dinoflagellates, which are responsible for more than 80% of harmful algal blooms in coastal waters, are competitive in low-phosphate environments. However, the specific acclimated phosphorus strategies to adapt to phosphorus deficiency in dinoflagellates, particularly through intracellular phosphorus metabolism, remain largely unknown. Comprehensive physiological, biochemical, and transcriptomic analyses were conducted to investigate intracellular phosphorus modulation in a model dinoflagellate, Prorocentrum shikokuense, with a specific focus on membrane lipid remodeling and autophagy in response to phosphorus deficiency. Under phosphorus deficiency, P. shikokuense exhibited a preference to spare phospholipids with nonphospholipids. The major phospholipid classes of phosphatidylcholine and phosphatidylethanolamine decreased in content, whereas the betaine lipid class of diacylglyceryl carboxyhydroxymethylcholine increased in content. Furthermore, under phosphorus deficiency, P. shikokuense induced autophagy as a mechanism to conserve and recycle cellular phosphorus resources. The present study highlights the effective modulation of intracellular phosphorus in P. shikokuense through membrane phospholipid remodeling and autophagy and contributes to a comprehensive understanding of the acclimation strategies to low-phosphorus conditions in dinoflagellates. [Display omitted] •P. shikokuense effectively modulates cellular P resources under P deficiency.•P. shikokuense spares and recycles phospholipids under P deficiency.•PC and PE increase whereas DGCC decreases in content under P deficiency.•P. shikokuense triggers autophagy under P deficiency.